2010
DOI: 10.1002/14651858.cd006605.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term opioid management for chronic noncancer pain

Abstract: Many patients discontinue long-term opioid therapy (especially oral opioids) due to adverse events or insufficient pain relief; however, weak evidence suggests that patients who are able to continue opioids long-term experience clinically significant pain relief. Whether quality of life or functioning improves is inconclusive. Many minor adverse events (like nausea and headache) occurred, but serious adverse events, including iatrogenic opioid addiction, were rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
162
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(168 citation statements)
references
References 94 publications
3
162
0
3
Order By: Relevance
“…23 % of patients discontinued THC/CBD spray due to AEs. By contrast, a meta-analysis of long-term opioid use for chronic non-cancer pain showed 34 % of patients discontinued strong oral opioids due to AEs [30]. No increase in intoxication was observed with long-term use of THC/CBD spray and no new significant safety issues were raised as a result of the study.…”
Section: Discussionmentioning
confidence: 84%
“…23 % of patients discontinued THC/CBD spray due to AEs. By contrast, a meta-analysis of long-term opioid use for chronic non-cancer pain showed 34 % of patients discontinued strong oral opioids due to AEs [30]. No increase in intoxication was observed with long-term use of THC/CBD spray and no new significant safety issues were raised as a result of the study.…”
Section: Discussionmentioning
confidence: 84%
“…Die in versorgungsnäheren unkontrollierten Studien erhobenen Schmerzlinderungen sind eher geringer [12,13,14,15,16,17,18] als in randomisierten kontrollierten Studien ermittelte Effekte.…”
Section: Wirkungsprognose Ohne Gewährunclassified
“…A review of studies on patients with chronic pain found nonadherence rates ranged from 2% to 53% [40•]. A separate review found that a sizeable percentage of patients on long-term opioid therapy discontinue its use [41]. Even if they are effective, patients may discontinue opioids for a variety of reasons, including side effects, a lack of efficacy (at the prescribed level or in general), and fear of addiction [42].…”
Section: Optimizing Opioid Prescribing Practices To Increase Benefitsmentioning
confidence: 99%